Empowering examiners to develop doctoral assessment literacy: a situated learning perspective - Tan, Wee Chun (Frontiers in Education, 2024)
Doctoral examiners play a pivotal role in upholding academic standards; therefore, they must be supported in their work. Drawing on situated learning theory, this paper proposes a conceptual training framework to empower examiners, particularly those participating in the PhD viva. The framework comprises three key initiatives: a professional development programme, a peer review, and an accreditation programme. The paper further highlights the potential benefits of the training initiatives and discusses implementation challenges aimed at fostering examiners' continuous professional development, promoting a deeper understanding of assessment literacy, and maintaining the overall quality of doctoral assessment.